he realization of corn productive potential at growth regulators’ foliar application - Filonenko, S.; Tyshchenko, M.; Popov, O. (Scientific Progress & Innovations, 2022)
The application of plant growth regulators has long become production necessity of cultivation technologies for many crops of the world agriculture including corn. Modern plant growth regulators are used for treating plants to initiate changes in the processes of their activity to improve the quality of plant material, increase yields, and to make harvesting and storage easier. Activating numerous biological processes in plant organisms and strengthening cell membrane permeability growth regulators assist in maximal realization of potential productivity by crops. Taking into account the fact that at present many various growth stimulating preparations have appeared on the market, it is important to choose the best of them for a specific grain corn hybrid that is cultivated in the specific soil and climatic zone. The purpose of our research was to study the impact of Florid Fresh, Aminostym, and Atonic Plus plant growth regulators on corn grain productivity of mid-ripening DKC 4351 Max Yield hybrid at foliar application. For this aim, we were to solve the following tasks: to study the impact of Florid Fresh, Aminostym, and Atonic Plus plant growth regulators on corn grain productivity of mid-ripening DKC 4351 Max Yield hybrid; to study the peculiarities of corn plants’ growth and development depending on foliar application of the investigated growth regulators. As a result of the conducted studies, it has been established that during the years of research corn plant leaf-area duration turned out to be the largest in all terms of making calculations in the variant, on which Atonic Plus growth regulator was applied outside root at a dose of 0.2 l/ha. Foliar application of Florid Fresh, Aminostym, and Atonic Plus positively affected corn plant height. During the years of experiments, the highest corn plants (230 cm) were found on the plots where Atonic Plus growth regulator was applied outside root. Plant height in the control variant was only 193 cm. The activating of corn plants’ photosynthetic activity and optimizing of various bio-chemical processes after growth regulators’ foliar application positively affected the crop grain yield. After three years, it turned out to be the maximal (10.02 t/ha) in the variant, where Atonic Plus growth regulator was used at a dose of 0.2 l/ha. The corresponding indicator turned out to be somewhat lower in the variants at Florid Fresh and Aminostym growth regulators’ foliar application – 9.47 and 8.92 t/ha, respectively. The lowest yields during the years of experiments were obtained from the control variant plots (8.01 t/ha) on which growth regulators were not used.